Search for Conditions to Detect Epigenetic Marks and Nuclear Proteins in Immunostaining of the Testis and Cartilage. (19th March 2014) - Ideno, Hisashi; Shimada, Akemi; Kamiunten, Taichi; Imaizumi, Kazuhiko; Nakamura, Yoshiki; Kimura, Hiroshi; Araki, Ryoko; Abe, Masumi; Nakashima, Kazuhisa; Nifuji, Akira
Abstract : The localization of nuclear proteins and modified histone tails changes during cell differentiation at the tissue as well as at the cellular level. Immunostaining in paraffin sections is the most powerful approach available to evaluate protein localization. Since nuclear proteins are sensitive to fixation, immunohistochemical conditions should be optimized in light of the particular antibodies and tissues employed. In this study, we searched for optimal conditions to detect histone modification at histone H3 lysine 9 (H3K9) and H3K9 methyltransferase G9a in the testis and cartilage in paraffin sections. In the testis, antigen retrieval (AR) was indispensable for detecting H3K9me1 and me3, G9a, and nuclear protein proliferating cell nuclear antigen (PCNA). With AR, shorter fixation times yielded better results for the detection of G9a and PCNA. Without AR, H3K9me2 and H3K9ac could be detected at shorter fixation times in primary spermatocytes of the testis. In contrast to the testis, all antibodies tested could detect their epitopes irrespective of AR application in the growth plate cartilage. Thus, conditions for the detection of epigenetic marks and nuclear proteins should be optimized in consideration of fixation time and AR application in different tissues and antibodies.